Agama Dan Pembentukan Cara Pandang Serta Perilaku Hidup Masyarakat - Joko Santoso; Yossita Wisman (FKIP Universitas Palangka Raya, 2020)
Religion is one of the most decisive factors in promoting the values and virtues of life in society. Human and Religion are a couple who always color life. There is no human who is not religious. Religion is part of human life. When religion influences life, at the same time behavior will affect one's life. Through its religious teachings and practices, religion directs the perspective of humans and society. In this article the author wants to discuss how religion plays the role of forming this perspective. The author focuses this study on ritual activities, Scriptures and ethical teachings that are generally carried out in every religion in teaching values. The purpose of this discussion is to raise the reader's awareness about the relevance of religion in human life and the importance of paying attention to the contents of religious teachings in order to promote the common good for all creation.